(untitled) (Research, Society and Development, 2023)
Introduction: Odontogenic infections are commonly found in the oral and maxillofacial region. Due to the diversity of the oral microbiota, they are caused by polymicrobial chains, which initially can settle in the dental tissues and evolve rapidly and progressively. Objective: To investigate some of the main odontogenic infections, analyzing their etiology, diagnosis and the most efficient forms of treatment in order to contribute to a better understanding of the clinical picture and its resolution. Methodology: The search strategies were structured from the databases: PubMed and MEDLINE, Google Scholar, SciELO and LILACS using the descriptors: "Focal Dental Infection", "Dental Infection Control", "Ludwig’s Angina", "Antibiotic Prophylaxis" and "Pathology, Oral". Studies were found from 2016 to 2023, in Portuguese, English and Spanish languages, excluding those performed on animals, without results or unpublished, and those that did not comprise odontogenic infections and hospitalized patients. Results: For this review 31 articles were collected, 25 of which were included for the development of the study. Discussion: The selected studies confirm the complexity of the symptomatology of odontogenic infections, which is predominantly composed of edema, erythema, pain, fever and trismus. However, with the evolution of the infectious process, there may be formation of acute or chronic abscess, besides the possible need for hospitalization. Early diagnosis, based on clinical and complementary exams, enables treatment, which combines surgical drainage, antibiotic therapy, and removal of the infectious cause. Conclusion: Anatomical knowledge, as well as professional training in prevention, diagnosis and treatment, is essential to mitigate the severity of these infections.